![\tan x+\cot x=\csc x.\sec x](https://img.qammunity.org/2023/formulas/mathematics/college/zg6idt7h4s29lfk3vanxjz9vvny95kat5o.png)
Let us change tan x and cot x to sin x and cos x
![\begin{gathered} \because\tan x=(\sin x)/(\cos x) \\ \because\cot x=(\cos x)/(\sin x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uc1ddmsvcyh2jqomm0l9wxn4s5k48iebl8.png)
Substitute them on the left side
![LHS=(\sin x)/(\cos x)+(\cos x)/(\sin x)=(\sin^2x+cox^2x)/(\cos x\sin x)](https://img.qammunity.org/2023/formulas/mathematics/college/nyxswcs68vklkiguyjgtdizwvtg2q13u6y.png)
I multiplied the denominators and multiply each numerator by the opposite denominator
![\because\sin ^2x+cox^2x=1](https://img.qammunity.org/2023/formulas/mathematics/college/m8zpash4ef03ospovrdo3ku4rz9w64d46q.png)
![\therefore L.H.S=(1)/(\sin x\cos x)](https://img.qammunity.org/2023/formulas/mathematics/college/jefdnr4au3241w3tpf0lv67cevxr9k63t8.png)
Now we will work on the right hand side
![\begin{gathered} \because\csc x=(1)/(\sin x) \\ \because\sec x=(1)/(\cos x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jwms0hqwgu5sytcrh2u6aa3dootx0nwxpw.png)
Substitute them on the right side
![\because R.H.S=(1)/(\sin x)*(1)/(\cos x)=(1)/(\sin x\cos x)](https://img.qammunity.org/2023/formulas/mathematics/college/w2yknm46cccbzueed540ejxo933ooilfl9.png)
The L.H.S = R.H.S = 1/(sin x cos x)